Self‐Assembled Multinuclear Complexes Incorporating 99mTc. Issue 41 (19th June 2018) - Frei, Angelo; Mokolokolo, Pennie P.; Bolliger, Robin; Braband, Henrik; Tsosane, Mampotso S.; Brink, Alice; Roodt, Andreas; Alberto, Roger
Abstract: Multinuclear complexes or clusters are rarely investigated in medicinal inorganic chemistry although they represent structural intermediates between molecules and nanomaterials. We present in this report two strategies towards 99m Tc‐containing clusters. In a pre‐assembly approach, the preformed but incomplete cluster fragment [Re3 (μ2 ‐OH)3 (μ3 ‐OH)(CO)9 ] − reacts with [ 99m Tc(CO)3 ] + to the highly stable [ 99m TcRe3 (μ3 ‐OH)4 (CO)12 ] cube. The same structure self‐assembles when reacting the mononuclear Re and 99m Tc precursors in one pot. Integrating the coordinating OH groups from Schiff bases in this concept leads straight to dinuclear, mixed‐metal complexes of the type [ 99m TcRe(μ2 ‐O^N‐R 1 )2 (CO)6 ] in quantitative yields. Both strategies are unprecedented and open a future path towards clusters, incorporating a 99m Tc radiolabel while being decorated with targeting or cytotoxic moieties. Abstract : There isn′t just one way : The synthesis of multinuclear 99m Tc‐containing complexes and clusters through pre‐assembly and self‐assembly approaches represents two unprecedented strategies in nuclear imaging and bioorganometallic chemistry (see figure).